![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
#)Trả lời :
a) \(\frac{-1}{2}+\frac{2}{7}-\frac{5}{28}\)
\(=\frac{-3}{14}-\frac{5}{28}\)
\(=\frac{-11}{28}\)
b) \(5\frac{3}{4}+\left(\frac{1}{9}-1\frac{3}{4}\right)\)
\(=\left(5\frac{3}{4}-1\frac{3}{4}\right)+\frac{1}{9}\)
\(=4+\frac{1}{9}\)
\(=4\frac{1}{9}=\frac{37}{9}\)
c) \(\frac{-5}{7}x\frac{2}{11}+\frac{-5}{7}x\frac{9}{11}+3\frac{5}{7}\)
\(=\frac{-5}{7}x\left(\frac{2}{11}+\frac{9}{11}\right)+3\frac{5}{7}\)
\(=\frac{-5}{7}x1+3\frac{5}{7}\)
\(=\frac{-5}{7}+3\frac{5}{7}\)
\(=\frac{-5}{7}+\frac{26}{7}\)
\(=\frac{21}{7}=3\)
#~Will~be~Pens~#
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x2 + 5x = 0
=> x.(x + 5) = 0
=> x = 0 hoặc x + 5 = 0
=> x = 0 hoặc x = -5
b) 1/21 + 1/28 + 1/36 + ... + 2/x(x + 1) = 2/9
=> 2/42 + 2/56 + 2/72 + ... + 2/x(x + 1) = 2/9
=> 2 × [1/6×7 + 1/7×8 + 1/8×9 + ... + 1/x(x + 1)] = 2/9
=> 1/6 - 1/7 + 1/7 - 1/8 + 1/8 - 1/9 + ... + 1/x - 1/x + 1 = 2/9 : 2
=> 1/6 - 1/x + 1 = 2/9 × 1/2 = 1/9
=> 1/x + 1 = 1/6 - 1/9
=> 1/x + 1 = 3/18 - 2/18
=> 1/x + 1 = 1/18
=> x + 1 = 18
=> x = 17
![](https://rs.olm.vn/images/avt/0.png?1311)
Bạn tham khảo cách của mình!
\(\frac{2}{15}+\left(\frac{5}{9}-\frac{6}{9}\right)\)
\(=\frac{2}{15}-\frac{1}{9}\)
\(=\frac{6}{45}-\frac{5}{45}\)
\(=\frac{1}{45}\)
Chúc bạn
Học tốt!
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm:
\(\left|x^2-2\right|+\left|2-x^2\right|=28\)
\(\Leftrightarrow\left|x^2-2\right|+\left|x^2-2\right|=28\)
\(\Leftrightarrow2\left|x^2-2\right|=28\)
\(\Leftrightarrow\left|x^2-2\right|=14\)
\(\Leftrightarrow\orbr{\begin{cases}x^2-2=14\\x^2-2=-14\end{cases}\Leftrightarrow}\orbr{\begin{cases}x^2=16\\x^2=-12\left(vl\right)\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=4\\x=-4\end{cases}}\)
\(2A=2+2^2+2^3+...+2^{10}\)
\(2A-A=A\)
\(A=\left(2+2^2+2^3+...+2^{10}\right)-\left(1+2+2^2+...+2^9\right)\)
\(A=2^{10}-0-0-0-...-0-1\)
\(A=2^{10}-1\)
Vậy \(5^{28}>2^{10}-1\)
Vì \(5>8;9>28\)